2017
DOI: 10.1016/j.ocemod.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficient non-hydrostatic modelling of 3D wave-induced currents using a subgrid approach

Abstract: Wave-induced currents are an ubiquitous feature in coastal waters that can spread material over the surf zone and the inner shelf. These currents are typically under resolved in non-hydrostatic wave-flow models due to computational constraints. Specifically, the low vertical resolutions adequate to describe the wave dynamics-and required to feasibly compute at the scales of a field site-are too coarse to account for the relevant details of the three-dimensional (3D) flow field. To describe the relevant dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…The nonhydrostatic (RANS‐based) wave‐flow model SWASH (version 5.01) was used, which is effectively a direct numerical implementation of the three‐dimensional Navier‐Stokes equations within a terrain following framework (Rijnsdorp et al, ; Smit et al, ; Zijlema et al, ). Here, the model was used in 2DV mode, for which the governing equations (momentum and continuity) are given by ut+italicuux+italicwuz+1ρphx+1ρpnhx=x)(υhux+z)(υvuz+1ρfv,x, wt+italicuwx+italicwwz+1ρpnhz=z)(υvwz+x)(υhwx, ux+wz=0, ζt+hζux=0, where f v , x is the (instantaneous) vegetation force, and ζ is the water surface elevation.…”
Section: Methodsmentioning
confidence: 99%
“…The nonhydrostatic (RANS‐based) wave‐flow model SWASH (version 5.01) was used, which is effectively a direct numerical implementation of the three‐dimensional Navier‐Stokes equations within a terrain following framework (Rijnsdorp et al, ; Smit et al, ; Zijlema et al, ). Here, the model was used in 2DV mode, for which the governing equations (momentum and continuity) are given by ut+italicuux+italicwuz+1ρphx+1ρpnhx=x)(υhux+z)(υvuz+1ρfv,x, wt+italicuwx+italicwwz+1ρpnhz=z)(υvwz+x)(υhwx, ux+wz=0, ζt+hζux=0, where f v , x is the (instantaneous) vegetation force, and ζ is the water surface elevation.…”
Section: Methodsmentioning
confidence: 99%
“…were obtained using laser Doppler anemometry (LDA) at 100 Hz at several cross-shore locations (8 and 7 locations for the spilling and plunging cases, respectively); note that due to the intermittent wetting / drying and presence of air bubbles during breaking, valid current measurements could not be obtained over the entire crest-to-trough region (only the lower portion). An additional advantage of the TK94 dataset is its historical use to assess the performance of a number of different models, which range from applications using Boussinesq wave models (e.g., Tissier et al, 2012, Cienfuegos et al, 2010, non-hydrostatic RANS models (e.g., Derakhti et al, 2016a, Rijnsdorp et al, 2017, Smit et al, 2013, and mesh-based CFD models such as OpenFOAM (e.g., Jacobsen et al, 2012, Brown et al, 2016, thereby providing an opportunity to place the present SPH simulations in the context of prior studies using other classes of models. was followed by a 1:8 beach covered with a porous mat to dissipate wave energy.…”
Section: Ting and Kirby (1994) -Plane Beachmentioning
confidence: 99%
“…These studies include those using 3D / 2DV phase-resolving wave-flow models solved on fixed grids using the same TK94 experiments to benchmark model performance, which can therefore provide valuable context to the present SPH results. Rijnsdorp et al (2017) and Derakhti et al (2016a) applied the multi-layered non-hydrostatic model approach to evaluate its ability to reproduce the mean current profiles observed in TK94 (see Figure 6 in the first, and Figure 3 and 4 in the latter study). While both studies found that the nonhydrostatic approach could reproduce the main features of the current profiles reasonably well, the results deviated significantly more than in the present study, with both an overprediction of the onshore transport in the crest region (by a factor of 2 for the plunging case) and with a similar overprediction of the offshore undertow transport (i.e., defined by more exaggerated belly-shaped profiles).…”
Section: Wave-driven Transport and Surf Zone Turbulencementioning
confidence: 99%
See 2 more Smart Citations